Development of Toddlers: Analyzing of the Utilization of the KIA Handbook In Mother In Indonesia - Evi Hasnita; Wenny Lazdia; Savitri Yolanda; Rina Mariyana (PT Publikasiku Academic Solution, 2023)
Developmental delays in children are still a serious problem in both developed and developing countries in the world. The number of developmental disorders in children under five in Indonesia is still quite high. In Indonesia 13 – 18 % of children under five experience developmental delays. The Maternal and Child Health Book (KIA) is an important communication tool and information medium for health workers, pregnant women, families, and the community. The purpose of this study is to analyze the use of the Maternal and Child Health Handbook with child development. The method used is Qualitative research. This study uses the in-depth interview method to find problems more openly. Participants in this study were mothers of toddlers. The sampling technique used was purposive sampling technique so that the participants could represent the characteristics of a population of 10 people. The results obtained by pregnant women who have a negative attitude tend not to use the Maternal and Child Health handbook properly and the theme of developmental disturbances for toddlers is that toddlers have unclear speech, and for other developments, there are no problems. It is recommended for parents to take advantage of the use of health books so that children's development runs optimally